Conflitos e Desafios de populaçoes tradicionais na Amazônia brasileira : o caso da Reserva Extrativista do Extremo Norte do Estado do Tocantins - Sousa, Dayane Rouse Neves (Mundo Agrario.)
This article analyzes the conflicts caused by virtue of the creation process Resex in the Far North until the year 2015. The chosen methodology was the case study, with information collected from written documents and interviews. The results indicate that after 24 years of existence of Resex the families still did not live within the area of this Conservation Unit, but in surrounding communities, which has contributed to the intensification in dispute for resources and conflicts between traditional population and farmers